The effect of academic level and academic specialization in improving the personal quality of students of the College of Education, Najran University - Abuelenin, Hanan Othman (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the level of personal quality among students of the College of Education at Najran University, and to identify the impact of the academic level and academic specialization on their personal quality level. The study followed the descriptive approach, and the tool was represented in the Personal Quality Scale, which consisted of (34) items. Prepared by the researcher, the study sample consisted of (300) students randomly selected and distributed as follows (180) Psychology program (100 students, 80 students), (80) Kindergartens program, (40) Home economics program, and the results of the study revealed that the level of personal quality Among the students of the College of Education, he obtained an overall average (2 out of 3),. a grade of (average). And at the level of dimensions; After good human relations with an average of (2.09), followed by then after high performance in the study with an average of (1.99), after positive personality traits obtained the highest average (1.94), all of which were verbal estimation (average). The results also found that there are no statistically significant differences between the mean scores of male and female students according to the gender variable (male - female), and there are statistically significant differences at the level of significance (0.01) between the mean scores of male and female students at the first academic level and male and female students at the fourth academic level on the quality scale Personality in favor of students of the fourth academic level, the existence of statistically significant differences at a level of significance (0.01) for the variable of specialization (Psychology program / Kindergarten program / Home economics program) in the variation of male and female students' grades on all dimensions of the personal quality scale and the total score of the scale in favor of students Psychology program. Based on the results, the researcher presented a set of recommendations and proposals to improve personal quality.
Keywords: Quality; Personality; Academic Specialization; Psychology Program; College of Education; Najran University